A comparison of tooth development between Iraqi and French Canadian children aged 4–14 years - Bushra Rashid Noaman; Hassan Abdulhadi Al-Kubaisi; Muhannad Dilshad Baqal; Muhammad Daham Gahetly (Dental Journal (Majalah Kedokteran Gigi), 2026)
Background: Teeth development is very important in pedodontic and orthodontic practices and even in forensic dentistry. Demirjian and Goldstein Maturation Standard proved its significance in many countries around the world. Purpose: This study was a comparison of teeth development between French-Canadian children and Iraqi children using the Demirjian method. Methods: A retrospective cross-sectional study was performed using 223 orthopantomograms (OPGs) for Iraqi patients aged 4-14 years (118 boys and 105 girls). The maturity standard put by Demirjian and Goldstein (1973) was used. Then the dental age (DA) for each chronological age (CA) in all age groups and compared with the Demirjian and Goldstein maturation standard for French-Canadian children. Statistical analysis used: SPSS was used. The statistical significance between Iraqi DA (IDA) and Demirjian DA (DDA) was tested at level p≤0.05 was significant. Results There was a significant underestimation in the age 4-7 years and a significant overestimation in the ages 8-11 years of Iraqi girls. While the girls aged 12-14 were the same DA as the French-Canadian children. The DA of the Iraq boys significantly precedes the ages of French-Canadian at ages 4-7 and significantly overestimated the Iraqi 9, 10, and 12 while at ages 8, 11, 13, and 14-year-old boys there was no statistically significant difference. Conclusion: Demirjian and Goldstein Maturation Standard cannot be considered standard for Iraqi children.